مقياس التفاضل الدلالي واستخداماته في دراسة الممارسات الجسدية -النسخة العربية - تركي احمد (Journal of Sport Science Technology and Physical Activities, 2024)
One of the most important advantages of the semantic differentiatial tool developed by Osgood is that it makes it possible to highlight the unconscious determinants of social practices, by adopting an indirect method of investigation. Despite its limited use in the social sciences, it remains less used in psychology than in the fields of marketing and economics, but the importance of the results cannot be neglected and they are fully adaptable to sociology and other areas. This little-known tool deserves to be approached theoretically by explaining its origin and its development within the Osgood team in the 1950s. We will show how to use this tool, modify the method of questioning, presentation and interpretation results, and some of its applications in the field of motor skills. Its multiple possibilities of use in many fields give this tool a wide application which undoubtedly allows us to patiently explore the psychosocial aspects still hidden in the field of games and sport. Through this article, we will try to facilitate the understanding and explanation of the tool, while supporting it by mentioning some intercultural studies which were carried out by members of the JPL research team in Paris, under the direction of Professor Pierre Parlebas, whose current work is part of it. These studies aimed to determine the importance of certain sports and games and to study the possible relationship between their structures and the pleasure of action. ا